Preparation method and application of gel adsorption material of sodium alginate-embedded PNAGA-bamboo charcoal-green algae active cells

By engaging the gel adsorption material of PNAGA-bamboo charcoal-green algae active cells in sodium alginate, combined with ultrasonic assistance, the problems of small adsorption capacity and large consumption in the prior art are solved, and efficient and reusable Adsorption effect and reduce energy consumption and cost.

CN118304869BActive Publication Date: 2025-02-14YANGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410606331.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-16
Publication Date
2025-02-14
Estimated Expiration
2044-05-16

AI Technical Summary

Technical Problem

The prior art has problems such as small adsorption capacity, large consumption, difficult regeneration or high cost, and short effective life when dealing with waste liquids containing cationic dyes.

Method used

The gel adsorption material used to embed PNAGA-bamboo charcoal-green algae active cells is enhanced by ultrasonic assistance, and biomass is accumulated during the adsorption process to achieve secondary utilization.

Benefits of technology

It achieves efficient and reusable adsorption effect, reduces energy consumption and costs, expands the scope of application, and has high research value and application advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118304869B_ABST
    Figure CN118304869B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and oil production application of a gel adsorption material of sodium alginate-embedded PNAGA-bamboo charcoal-green algae active cells, wherein low-concentration liquid PNAGA is mixed with a certain concentration of green algae liquid and bamboo charcoal, NaHCO₃ and glacial acetic acid are added to form bubbles, and then a cross-linking agent CaCl₂ is added to form gel spheres. Then the material is left to stand for a period of time to age, and is taken out and repeatedly rinsed with deionized water for several times before reuse. The sodium alginate-embedded-bamboo charcoal-algae / PNAGA hydrogel composite material provided by the invention can be reused, raw materials can be recycled, and the structure is stable, the energy consumption is low, the treatment effect is good, and the application range is wide. The material can increase the performance of adsorbing sewage dyes in coordination with ultrasound, and can accumulate and produce lipids at the same time, and has high research value and application advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and in particular relates to a preparation method and application of a lipid gel adsorption material for treating waste liquid containing cationic dyes, absorbing odorous gases and generating the same. Background Art

[0002] Rapid industrial development has led to the need for wastewater treatment. Organic dyes are widely used in papermaking, textile and plastic industries as the main industrial dyes. Some organic dyes are highly toxic and difficult to degrade. They are discharged into the natural environment with industrial wastewater, causing serious water pollution.

[0003] At present, adsorption is considered to be one of the most effective methods for removing dyes from aqueous solutions. However, the traditional adsorption / desorption process takes a long time to reach equilibrium, has a small adsorption capacity, high consumption, difficult or high cost for regeneration, and a short effective life. Summary of the invention

[0004] Purpose of the invention: In order to solve the technical problems existing in the prior art, the present invention provides a preparation method and application of a gel adsorption material of sodium alginate-embedded PNAGA-bamboo charcoal-green algae active cells. The sodium alginate-embedded-bamboo charcoal-algae / PNAGA hydrogel composite material provided by the present invention can be reused and recycled, and has the advantages of stable structure, high mechanical strength, low energy consumption, good treatment effect, wide application range, etc. This material can enhance the performance of adsorbing sewage dyes in coordination with ultrasound, and can accumulate and produce lipids at the same time, and has high research value and application advantages.

[0005] Technical solution: To achieve the above invention purpose, the present invention adopts the following technical solution: a method for preparing a gel adsorption material of sodium alginate-embedded PNAGA-bamboo charcoal-green algae active cells, comprising the following steps:

[0006] S1, adding NAGA monomer and initiator KPS into deionized water, and placing it at a temperature of 60±5°C for polymerization reaction for at least 3 hours to obtain a polymerized liquid PNAGA hydrogel for standby use;

[0007] S2, centrifuging the green algae liquid, removing the supernatant and collecting the green algae cells, adding BG11 medium for washing, and the obtained green algae-containing algae liquid is stably placed in the BG11 medium for at least 15 minutes;

[0008] S3, adding sodium alginate to the algae liquid containing green algae obtained in step S2, stirring and dispersing the mixture evenly, to obtain a sodium alginate solution containing green algae cells;

[0009] S4, adding bamboo charcoal powder to the sodium alginate solution containing green algae cells obtained in step S3, and stirring to disperse the mixture evenly;

[0010] S5, continue to add the PNAGA hydrogel obtained in step S1, stir and disperse evenly, then add sodium dodecyl sulfate SDS and sodium bicarbonate, and stir rapidly for more than 2 hours to allow air to be enclosed therein;

[0011] S6, transferring the solution obtained in step S5 into a syringe, and then dripping a mixed solution containing calcium chloride solution and glacial acetic acid through a needle to form gel beads by cross-linking reaction, with the injection dripping flow rate being 30-40 mL·h –1 ;

[0012] S7, taking out the aged gel beads, washing them with deionized water for several times to obtain the target product.

[0013] Preferably, the concentration of PNAGA in the PNAGA hydrogel in step S1 is 1-5wt%; the concentration of green algae cells in the sodium alginate solution containing green algae cells obtained in step S3 is 5×10 5 / ml-5×10 6 Pieces / ml.

[0014] Preferably, 15-30 parts by weight of PNAGA hydrogel and 2-10 parts by weight of bamboo charcoal are contained in 100 parts by weight of sodium alginate.

[0015] Preferably, the concentration of the calcium chloride solution in step S6 is 2-10wt%.

[0016] Furthermore, the present invention also provides a method for treating wastewater organic matter by adsorption, which uses the above-mentioned gel adsorption material to co-adsorb with ultrasound while in contact with wastewater, and the ultrasound frequency is 5-20MHz. The ultrasound of the present invention utilizes cavitation to increase the adsorption / desorption capacity of the material, which is more efficient and economical, and does not produce secondary pollution.

[0017] Furthermore, in the mixed solution of step S6, the concentration ranges of calcium chloride and glacial acetic acid are 2% (w / v)-10% (w / v) and 5% (w / v)-10% (w / v), respectively.

[0018] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0019] 1. The composite gel bead adsorption material of the present invention innovatively embeds PNAGA-bamboo charcoal-green algae in sodium alginate. PNAGA embedding does not require a pore-forming agent to form a porous three-dimensional structure, and can dynamically relay gel-sol transformation at around 80°C, so that the material can be reused; the rich functional groups (amino, hydroxyl and carboxyl) of the green algae cell wall can form bonds or electrical adsorption with organic pollutants, and at the same time, cavitation sonosensitization can increase the adsorption capacity under the assistance of ultrasound; and the biomass bamboo charcoal improves the mechanical strength of the adsorption beads while improving the adsorption capacity.

[0020] 2. The sodium alginate-encapsulated PNAGA-bamboo charcoal-green algae active cell composite gel ball adsorption material prepared by the present invention does not require the addition of a pore-forming agent or high-temperature calcination, has a simple preparation method, and has the advantages of low energy consumption, good treatment effect, wide application range, low cost, etc., and has high research value and unique application advantages.

[0021] 3. The sodium alginate-embedded PNAGA-bamboo charcoal-green algae active cell composite gel ball adsorption material of the present invention can undergo gel-sol transformation at about 80° C. through dynamic relay, can withstand a high hydraulic load, is easy to recycle, and has high reusability.

[0022] 4. The sodium alginate-encapsulated PNAGA-bamboo charcoal-green algae active cell composite gel ball adsorption material prepared by the present invention can accumulate biomass during the adsorption process, and can be broken by ultrasonic acid hydrolysis to produce oil for secondary utilization, thereby realizing the conversion and regeneration of bioenergy. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a morphology diagram of the gel adsorption material prepared in Example 1 of the present invention;

[0024] Figure 2 The test result curves of the gel adsorption material prepared in the examples of the present invention for adsorbing 50 ppm of crystal violet MG, A represents the adsorption curve of the gel beads prepared in Example 1, and B represents the adsorption curve of the sodium alginate gel beads prepared in Example 2.

[0025] Figure 3 The graph is a test result curve of the gel adsorption material prepared in the embodiment of the present invention for adsorbing 25 ppm crystal violet CV, C represents the adsorption curve of the gel beads prepared in Example 1, and D represents the adsorption curve of the sodium alginate gel beads prepared in Example 2.

[0026] Figure 4 A bar graph showing the performance of cyclic adsorption of the gel adsorption material prepared in accordance with an embodiment of the present invention;

[0027] Figure 5 These are confocal fluorescence micrographs of the gel adsorption material prepared in an embodiment of the present invention before and after BODIPYTM 505 / 515 staining, wherein A is before staining and B is after staining. DETAILED DESCRIPTION

[0028] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application. Example

[0029] The specific steps of preparing the sodium alginate-embedded PNAGA-bamboo charcoal-green algae active cell gel ball adsorption material in this embodiment are:

[0030] (1) 1 g of NAGA monomer and 0.02 g of KPS were completely dissolved in 8 g of deionized water. The solution was then injected into an artificial mold and placed in an oven at 60 °C for 4 hours for polymerization to obtain PNAGA hydrogel in a polymerized liquid state.

[0031] (2) Centrifuge the green algae solution, discard the supernatant, collect the algae cells, and add BG11 culture medium to wash them. Let the washed algae solution stand for 15-20 minutes to allow the algae cells to stabilize in the culture medium;

[0032] (3) Use an optical microscope to count the algal cells in the cleaned algal solution and control the algal cell concentration;

[0033] (4) Take 30 ml of the algae solution containing green algae cells in step (3) and add sodium alginate. Use a stirrer to stir evenly to ensure that the algae cells are evenly distributed in the sodium alginate solution.

[0034] (5) Add 15 mg of bamboo charcoal powder to the sodium alginate solution containing green algae in step (4), and stir evenly with a stirrer to make the bamboo charcoal powder evenly distributed in the sodium alginate solution containing green algae cells;

[0035] (6) taking the sodium alginate solution containing bamboo charcoal and green algae in step (5) and adding the 2 wt % PNAGA hydrogel prepared in step (1), stirring evenly with a stirrer to ensure that each phase is evenly distributed;

[0036] (7) Take the sodium alginate solution containing PNAGA, bamboo charcoal, and green algae in step (6), add 60 mg SDS and 0.3 g NaHCO 3 , the solution was stirred continuously for about 2 h to allow air to be entrapped in it.

[0037] (8) Prepare calcium chloride solution with deionized water;

[0038] (9) Slowly dripping the mixed solution prepared in step (7) into the calcium chloride solution in step (8) using an injection to form small spherical balls;

[0039] (10) Add NaOH to the solution in step (9), treat with ultrasound for 10 min, and allow to stand for 30-60 min to age.

[0040] (11) Filter out the solidified gel beads with a mesh bag and wash them 2-3 times with deionized water to remove free iron ions on the surface. Example

[0041] The specific steps for preparing gel beads containing only sodium alginate in this embodiment are:

[0042] (1) Weigh 0.6 g of sodium alginate and add it to 30 ml of deionized water and stir to form a sodium alginate gel solution.

[0043] (2) Weigh 4 g of anhydrous calcium chloride and add it to 100 ml of deionized water to prepare a calcium chloride solution.

[0044] (3) Use a 2.5 ml injection to slowly drip the sodium alginate gel prepared in step (1) into the calcium chloride solution in step (2) to form small spheres. The diameter of the spheres is generally 2-3 mm.

[0045] (4) The pellets are placed in the calcium chloride solution in step (5) for 30-60 minutes to age them.

[0046] (5) Filter out the solidified gel beads with a mesh bag and wash them 2-3 times with deionized water to remove free iron ions on the surface.

[0047] Evaluation of the performance of the gel beads prepared in Examples 1 and 2 in removing organic pollutants.

[0048] (1) Test method: A malachite green (MG) solution with an initial concentration of 50 mg / L and a crystal violet (CV) solution with an initial concentration of 25 mg / L were prepared to simulate organic polluted liquid wastewater, and the gel beads prepared in Examples 1 and 2 were added respectively. Under the condition of a solid-liquid ratio of 3:10, an adsorption experiment was carried out for 2 h using a magnetic stirrer.

[0049] (2) Calculation of absorption performance: After the experiment, the removal rate of organic pollutant liquid and the adsorption amount of gel beads are calculated as follows:

[0050] Removal rate calculation formula: Formula (1)

[0051] In formula (1), ŋ represents the removal rate (%); C0 and Ce represent the initial concentration of MG before treatment and the concentration of MG after treatment, respectively (mg / L).

[0052] Adsorption capacity calculation formula Formula (2)

[0053] In formula (2), Qe represents the adsorption capacity, mg / g; C0 and Ce represent the initial concentration of MG before treatment and the concentration after treatment, respectively (mg / L); V represents the volume of the polluted liquid, L; and m represents the encapsulation amount of PNAGA, green algae and bamboo charcoal, g.

[0054] The experimental results of MG adsorption are shown in Figure 2 As shown in the figure, A represents the adsorption curve of the gel beads prepared in Example 1, and B represents the adsorption curve of the sodium alginate gel beads prepared in Example 2. Figure 2 It can be seen that: (1) the gel beads encapsulating PNAGA, green algae and bamboo charcoal have better effects; (2) when the optimal formula is used, the removal rate of organic dyes reaches 79.27% ​​in 3 hours, and the adsorption capacity reaches 226.83 mg / g.

[0055] The experimental results of adsorption CV are as follows Figure 3 As shown in the figure, C represents the adsorption curve of the gel beads prepared in Example 1, and D represents the adsorption curve of the sodium alginate gel beads prepared in Example 2. Figure 3 It can be seen that: (1) the gel beads encapsulating PNAGA, green algae and bamboo charcoal have better effects; (2) when the optimal formula is used, the removal rate of organic dyes reaches 93.6% in 3 hours, and the adsorption capacity reaches 75.28 mg / g.

[0056] The cyclic adsorption performance of the prepared gel beads is as follows Figure 4 It can be seen that the material prepared by the present invention still has high adsorption efficiency after 5 cycles.

[0057] (3) Flow cytometric analysis of oil production

[0058] In order to investigate the oil accumulation of Chlorella cells, the algae cells were stained with BODIPYTM 505 / 515 and observed under a confocal fluorescence microscope. Figure 5 As shown: the dye can dye the oil efficiently. The more green the material is, the more oil it absorbs and accumulates. Figure 5 A in the figure is the oil production of microalgae that has not been coated with this material. Figure 5 B is the oil production of microalgae wrapped by the material, so it can be shown that the material can accumulate oil and produce oil well when adsorbing pollutants. The sodium alginate-embedded PNAGA-bamboo charcoal-green algae active cell composite gel ball adsorption material prepared by the present invention can accumulate biomass during the adsorption process, and can be used to break the wall by ultrasonic acid hydrolysis to produce oil, which can be reused to achieve the conversion and regeneration of bioenergy, and can be used as a renewable energy source for biofuel production, and can produce oil through the accumulation of microalgae biomass.

[0059] In the PNAGA hydrogel of the present invention, sodium alginate reacts with glacial acetic acid to form carbon dioxide during the calcium ion crosslinking process, thereby obtaining a three-dimensional interconnected structure in the gel. The introduction of SDS reduces the tension of the gas-liquid interface, and forms interconnected macropores rather than dense small pores inside the gel, thereby making the foam pores more stable. In the initial stage of pore formation, there are macropores, small pores, micropores and mesopores, and the biomass bamboo charcoal is adsorbed at the adsorption sites of the small pores and micropores to provide a skeleton support for the pores.

[0060] The sodium alginate solution containing PNAGA-bamboo charcoal and green algae in the present invention is cross-linked under the action of calcium chloride and glacial acetic acid to form embedded porous gel spheres, and the internal cross-linked network of the gel spheres is strengthened by in-situ aging to improve the mechanical strength thereof.

[0061] The adsorption material provided by the present invention can not only utilize the green algae that originally affects the water quality, but also give full play to its adsorption of organic pollutant liquid. And it can be embedded and reused, reducing the influence of hydraulic migration on the green algae. With the assistance of ultrasound, it plays the role of cavitation sonosensitivity to increase the adsorption capacity. Bamboo charcoal can increase the adsorption performance and mechanical strength of the small balls. PNAGA gel undergoes gel-sol transformation through dynamic dissociation of hydrogen bonds at about 80°C, so that the material can be reused and easily recycled. In addition, the bamboo charcoal-green algae small ball adsorption material embedded with PNAGA gel prepared by the present invention does not need to add pore-forming agents or high-temperature roasting, and the preparation method is simple, and has the advantages of low energy consumption, good treatment effect, wide application range, low cost, etc., and has high research value and unique application advantages.

[0062] This material has a capacity-increasing effect in adsorbing wastewater dyes under 10-20MHz ultrasonic conditions. The biomass accumulated during the adsorption process can be broken through ultrasonic acidolysis to produce oil and fat, which can be reused to achieve the conversion and regeneration of bioenergy.

[0063] The above descriptions are only some embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a gel adsorption material of sodium alginate-embedded PNAGA-bamboo charcoal-green algae active cells, characterized in that The following steps are involved: S1, adding NAGA monomer and initiator KPS to deionized water, and placing it at a temperature of 60±5°C for polymerization reaction for at least 3 hours to obtain a polymerized liquid PNAGA hydrogel for standby use; S2, centrifuging the green algae liquid, removing the supernatant and collecting the green algae cells, adding BG11 medium for washing, and the obtained green algae-containing algae liquid is stably placed in the BG11 medium for at least 15 minutes; S3, adding sodium alginate to the algae liquid containing green algae obtained in step S2, stirring and dispersing the mixture evenly, to obtain a sodium alginate solution containing green algae cells; S4, adding bamboo charcoal powder to the sodium alginate solution containing green algae cells obtained in step S3, and stirring to disperse the mixture evenly; S5, continue to add the PNAGA hydrogel obtained in step S1, stir and disperse evenly, then add sodium dodecyl sulfate SDS and sodium bicarbonate, and stir rapidly for more than 2 hours to allow air to be enclosed therein; S6, transferring the solution obtained in step S5 into a syringe, and then dripping a mixed solution containing calcium chloride solution and glacial acetic acid through a needle to form gel beads by cross-linking reaction, with the injection dripping flow rate being 30-40 mL·h –1 ; S7, taking out the aged gel balls, washing them with deionized water for several times, and obtaining a gel adsorption material of PNAGA-bamboo charcoal-green algae active cells embedded in sodium alginate.

2. The method for preparing the gel adsorption material of sodium alginate embedded PNAGA-bamboo charcoal-green algae active cells according to claim 1, characterized in that: The concentration of PNAGA in the PNAGA hydrogel in step S1 is 1-5wt%; the concentration of green algae cells in the sodium alginate solution containing green algae cells obtained in step S3 is 5×10 5 / ml-5×10 6 Pieces / ml.

3. The method for preparing the gel adsorption material of sodium alginate embedded PNAGA-bamboo charcoal-green algae active cells according to claim 1, characterized in that: 15-30 parts by weight of PNAGA hydrogel and 2-10 parts by weight of bamboo charcoal are contained in 100 parts by weight of sodium alginate.

4. The method for preparing the gel adsorption material of sodium alginate embedded PNAGA-bamboo charcoal-green algae active cells according to claim 1, characterized in that: The concentration of the calcium chloride solution in step S6 is 2-10wt%.

5. A method for treating wastewater organic matter by adsorption, characterized in that: The gel adsorption material prepared by the preparation method according to any one of claims 1 to 4 is co-adsorbed with ultrasound while in contact with wastewater, and the ultrasound frequency is 5-20 MHz.

Citation Information

Patent Citations

  • Method for preparing granular hydrogel type heavy metal adsorbent

    CN105944696A

  • Preparation method and application of sodium alginate embedded bamboo charcoal-green alga active cell gel bead adsorption material

    CN115869922A

  • Efficient adsorbent C (at) SA (at) CMC and preparation method and application thereof

    CN116173920A